Study of Spatial Structure of the Old Port Area of the Kingdom of Aceh in the West Coast of Aceh and its Sustainability System Case Study: Settlement Around Kuala Bubon, West Aceh District (International Journal of Architecture and Urbanism, 2025)
The Kuala Bubon area on the west coast of Aceh was one of the important ports during the XVII-XIX centuries of the Aceh Kingdom, which had a hinterland of royal economic commodities in the interior. Its current existence is as an important fishing area in West Aceh district, although it was destroyed during the 2004 tsunami. The difference in the role of the area can be seen in the difference in the structure of the area's space. This paper aims to explore the concept of the spatial structure of the region and the regional sustainability system in the context of the geographical environment and development policy. This paper is important related to climate change mitigation strategies related to the revitalization of old residential areas on the coast related to SDGs. point 11. The research approach is a phenomenological study of the history of settlements. The qualitative descriptive research method examines and interprets the eco-logic of important places in an area as an element forming the spatial structure of the area and understands the phenomenon of the development of the place until present day. The data consists of 3 types of topics: a) geographical conditions of the place, b) the spatial structure of the area, and c) data on regional development policies. The results showed that the condition of the bay waters and the position of the headland in the Kuala Bubon area has the potential to develop as a traditional port, which is connected to the interior with the hinterland activity center by the Kreung Bubon River. Thus, it formed a spatial structure with a linear pattern towards the interior (North-South). Plantation farming villages developed around the river. The period of the unitary state of the Republic of Indonesia until the XXI century with the 2004 tsunami disaster with the construction of infrastructure for the mainland West coast of Aceh that crossed the Kuala Bubon area, attracted the growth of villages around the road with a linear pattern (West-East) and a centralized pattern in Muara Kuala Bubon with developing aquaculture community. The role of rural villages is weakening. The conclusion of the study is that the shift in the orientation of the spatial structure of the area shows the pattern of the regional sustainability system which is related to 3 things: a) the right choice of place for a city traditionally and the ability to revitalize itself by managing natural potential in a contextual manner, b) political policy for regional development according to the potential of the place, and c) the high spirit of place from the community